Pengaruh Hormon LHRH-A dan 17α-MT Terhadap Respon Imun Non-Spesifik Induk Ikan Kerapu Lumpur, Epinephelus coioides - Fris Johnny; Agus Priyono; Des Roza (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The aim of this research was to find out the influence of the chronic hormone LHRH-a and 17α-MT on non-specific immune response of mangrove grouper, Epinephelus coioides broodstock. Female and male fish weight used in this experiment ranged 4.7-10.4 kg and 10.4-17.8 kg, respectively. The female fish were treated with hormone 17α-MT at a dosage of 50 µg/kg body weight, while the male fish treated with hormone LHRH-a at dosages of 50 and 100 µg/kg body weight. Fish were kept separately in two concrete tanks contained 100 m³ sea water, and 2 meters depth. The stocking density was 15 fishes/tank with male and female ratio 1 : 2. The blood samples were colected before treatment by hormone and every two months, subsequently. The non-specific immune response parameters evaluated were phagocytic activity (PA), phagocytic index (PI), and lysozyme activity (LA). Results indicated that chronic hormone could increase non-specific immune response especially phagocytic activity up to 17.3%.